2009
DOI: 10.3113/fai.2009.0933
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Function and Sports Activity after Total Ankle Arthroplasty

Abstract: This study showed that TAA improved the quality of life and that return to recreational activities was generally possible but the return to impact sport was rarely possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 30 publications
6
39
0
8
Order By: Relevance
“…In fact, there were 85% and 86% of patients, respectively, satisfied or very satisfied with the results of the operation [34].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there were 85% and 86% of patients, respectively, satisfied or very satisfied with the results of the operation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Three surgeons (MB, JAC, TJ) performed all operations using a standardized technique [5,6]. The goal was to restore a physiologic tibiocalcaneal axis and an anatomic joint line level.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly in Europe, the appearance of new-generation, mobile-bearing, cementless prostheses has renewed interest in TAA [5,11,24,33,48,[51][52][53]. The theoretical advantages of TAA compared with arthrodesis are maintaining joint ROM and restoring more normal kinematics in the hopes of providing the patient with greater comfort and better functional recovery [7,31,33,35,49]. The disadvantages are related to the risk of mechanical complications with failure sometimes requiring implant removal along with subsequent arthrodesis, which can be technically demanding and lead to a less satisfactory result than with primary arthrodesis [10,19,47].…”
Section: Introductionmentioning
confidence: 99%
“…Valderrabano et al found that the rate of sports participation increased postoperatively in patients undergoing TAR, however two subsequent studies found the rate of participation to be about the same before and after TAR [9][10][11][12]. Importantly though, in all three of these studies, more than half of patients with a TAR were participating in sports after surgery.…”
Section: Discussionmentioning
confidence: 79%
“…The few studies that have looked at postoperative physical activity and athletic participation rates following TAR describe varying results and provide little guidance for surgeons [9][10][11][12]. While it appears that both physical activity and sports participation tend to increase after total ankle replacement, no one has actually studied surgeon comfort, rationale, or preference regarding return to these specific activities.…”
Section: Introductionmentioning
confidence: 91%